Reverse Evidence System in Corruption Crime: Critical Analysis, Obstacles and Challenges - Arif Sahlepi, Muhammad; Mamanda Tarigan, Fitra; Abdul Rahman Maulana Siregar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research aims to discuss the legal arrangements of reverse evidence in corruption trials and comprehensively examine the obstacles and challenges of reverse evidence in corruption cases. The type of research is normative juridical, which discusses certain legal phenomena and analyses them based on laws or norms that live in society. The results of this study show that the reverse proof system is regulated in the provisions of Article 37, Article 37A, and Article 38B of Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Corruption, which states the defendant's obligation to prove otherwise against property owned not derived from the proceeds of corruption crimes. Reverse proof of corruption crimes has obstacles and challenges such as legal substance factors, focus of proof, inconsistency, violation of rights, and resistance of law enforcement. The challenges of reverse proof are: improving the performance, professionalism, and integrity of law enforcement officials, as well as the clarity of regulations to apply reverse evidence outside of corruption crimes such as narcotics and terrorism.